ANALISIS PERMASALAHAN PEMBELAJARAN IPA: STUDI KASUS DI SMPN 7 MUARO JAMBI - Jufrida Jufrida; Fibrika Rahmat Basuki; Frenki Rinaldo; Heni Purnamawati (Pendidikan Kimia Unimus, 2020)
This research aims to determine the problem of science learning in Junior High School. This research was conducted at the 7 Muaro Jambi Junior High School in the academic year 2018/2019. The study uses a qualitative approach with the case study type. The subjects of this research were 9 grade students of 7 Muaro Jambi Junior High School. The research instrument used observation sheets for science learning facilities, student and teacher questionnaire. Data was analyzed in a qualitative descriptively with an interactive analysis models (Huberman and Miles models). The results showed that the application of scientific approaches has not been optimal. The results of this study showed that the application of scientific approaches has not been optimal. Science learning still rarely use multimedia. Teachers rarely invite students to investigation or experiment to find the science concept. Students learn by memorizing the concepts found in the book or described by the teacher. Students have difficulty to explain the application of science concepts related to the phenomenon in daily life. Students' motivation and interest in science learning are low. Parents lack the attention and guidance of studying science at home to their children. The average time used to learn of science outside of the schools is < 2 hours/week. The school has laboratory equipment and science tectbooks are adequate to support the study of science.